Nitrogen-doped coal-based porous carbon: A one-step synthesis approach for superior anode performance in lithium-ion batteries - Jiang, Dongwei; Li, Songquan; Li, Xu; Jin, Yongzhong; Zhang, Zhengquan; Liu, Yonghong; Xu, Tao (Diamond and related materials, 2025)
Coal is considered as an ideal raw material for fabricating anode materials used in lithium-ion batteries (LIBs), due to its low cost and abundant availability. In this study, we report a synthesis method for nitrogen-doped coal-based porous carbon material (NPC) based on anthracite. By integrating chemical activation and nitrogen doping into a one-step process, high-performance anode materials for lithium-ion batteries have been successfully developed. This approach not only leverages the advantages of anthracite's low cost and abundant availability but also significantly enhances the electrochemical performance of the material through nitrogen doping and porous structure design. Specifically, the NPC anode material exhibits remarkable cycling stability, maintaining a discharge specific capacity of 488.5 mAh/g after 500 cycles at a high current density of 1 A/g. Additionally, the NPC anode exhibits outstanding rate capability, with 397.4 mAh/g at 1.0 A/g and 285.7 mAh/g at 2.0 A/g. These superior performances are not only related to the pore structure that can provide efficient channels for lithium ion transport, but also to the nitrogen doping that can enhance the conductivity of the material. This study offers an innovative and effective strategy for the design of high-performance anode materials for lithium-ion batteries, particularly in the context of utilizing low-cost and abundant raw materials to produce high-performance energy storage materials. [Display omitted] •The preparation process is very simple.•This approach leverages the advantages of anthracite’s low cost and abundant availability.•In this study, anthracite coal is used as raw material to produce porous carbon anode materials, which effectively reduces the damage caused by coal burning to the environment.